Critical thinking workshop and its effects on university students’ cognitive skills - Getrude Cosmas; Walton Wider; S.Intan Savitri; Dina Syakina (WHO Office in Azerbaijan, 2022)
In the era of the Industrial Revolution 4.0, critical and creative thinking skills are essential to fulfil industry’s demands and navigate challenging future lives, particularly among university students. University students need to enhance their cognitive skills by engaging in related programmes that can help to improve and develop their critical and creative thinking (CCT) skills. Although these types of thinking are nurtured in academic tasks, they might not be applied wholly by some students in academic settings. Some students merely use descriptive reading and writing because they find it more convenient and it can be conducted in a short time without burdening their cognitive functions. To examine this issue thoroughly, a one-day critical thinking (CCT) workshop was conducted with the aim of levelling up participants’ CT skills, including the two critical thinking elements of openness and reflection. The workshop was comprised of a critical thinking module, in which the participants discovered the concept and benefits of critical thinking in both academic and non-academic activities. A quasi-experimental study was conducted to examine the mean differences in the participants’ CT skills before and after they engaged in the activities of the CT workshop. The results showed that there were no significant differences between participants’ critical and creative skills before and after the workshop. Despite there being no significant differences, the participants stated that the one-day CT workshop could help them reflect on the benefits and ways of using critical and creative thinking skills in their academic and daily life activities. It was also found that the higher the participants’ CT skills, the higher their creative skills were both before and after the workshop. This showed that both types of thinking skills are related to each other, and students should take into consideration the importance of these cognitive skills and engage in relevant activities that may help enhance their cognitive skills in dealing with highly competitive and unexpected demands.